Distress level and its contributing factors among caregiver of adolescent cancer patients: a review - Che Abdullah, Che Azunie; Mohd Nordin, Ainul Syazwani; Triangsih, Devi (IIUM Press, 2025)
Distress is defined as a negative state in which an individual's coping mechanisms fail to restore physiological or psychological homeostasis. This condition may arise from severe or prolonged stressors, or from the cumulative impact of multiple stressors, resulting in adverse effects on the overall well-being. In this study, the stressors are identified as challenges faced by the parents as the main caregivers for an adolescent with cancer. Despite their strong desire to support and protect children, parents must cope with their own fears and concerns (distress), creating a dual crisis for them. Understanding this situation would help to improve the provision of support and service towards the care of adolescent cancer patients by improving the support needed by the caregivers in managing their child’s health. Hence, this study aimed to review the current literature of distress levels and its contributing factors among caregivers of adolescents diagnosed with cancer. Systematic searches from related databases have yielded 15 articles included in this review. Evidence reported that caregivers were affected with increased anxiety, depression, post-traumatic stress disorder, and decreased quality of life while caring for the patient. Five categories of contributing factors to the distress among caregivers were practical, social, emotional, cognitive, physical, and parenting problems. The findings could guide healthcare providers in addressing multiple dimensions of care when supporting parents of adolescents with cancer, thereby promoting holistic and comprehensive care